Tentacles - Smith, Roland (Scholastic London, 2011)
Marty and Grace are living with their Uncle Wolfe, a scientist fascinated by cryptids - creatures that appear in myths but haven't been proven to exist. The twins join Wolfe on a journey, on a huge (and possibly haunted) ship, in search of a rare giant squid. But someone on board is determined to sabotage the mission!